A method for preparing a lithium-ion battery positive electrode material coated with a solid electrolyte

By covering the surface of lithium -ion batteries on the surface of the positive electrode material, the solid electrolyte of titanium aluminum aluminum (LATP) is solved, the problem of decreased circulation life of the positive electrode material and the complex covering process, and the efficient covering and good electrochemical performance of the material.

CN116646523BActive Publication Date: 2025-01-28CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310752396.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2025-01-28
Estimated Expiration
2043-06-25

AI Technical Summary

Technical Problem

The application of existing lithium-ion battery positive electrode materials is limited by problems such as surface side reactions and particle microcracks, resulting in a decrease in cycle life. The existing coating process is complex, making it difficult to achieve industrial scale production.

Method used

The solid electrolyte titanium aluminum aluminum lithium (LATP) is used to cover the LinixCoym1-X-YO2 positive electrode material. The drying method is combined and mixed with low-temperature and high temperature.

Benefits of technology

The good magnification performance and cycle stability of the lithium -ion battery positive materials are realized, the service life of the material is significantly improved, and the process of process is simplified, which is suitable for industrialized scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116646523B_ABST
    Figure CN116646523B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium-ion battery positive electrode materials, and specifically relates to a method for preparing a lithium-ion battery positive electrode material coated with a solid electrolyte. The chemical composition of the positive electrode material includes a core LiNi x Co y M 1‑x‑y O2, wherein M is Mn or Al, x+y≤1 and a shell solid electrolyte lithium aluminum titanium phosphate (LATP). The solid electrolyte LATP is coated on the surface of the positive electrode material by a one-step calcination method. LATP is an excellent fast ion conductor with high safety and stability. The present method selects LATP as a coating modifier, which can not only improve the side reactions between the positive electrode material and the electrolyte during the cycle and the generation of cracks on the surface of the material by isolating the electrolyte and the positive electrode material, but also reduce the impedance of lithium ion transfer between the liquid phase and the solid phase, thereby increasing the ion transfer rate. The preparation method is simple, short in cycle, and suitable for industrial-scale production. The material exhibits excellent cycle performance at a cut-off voltage of 4.3V.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery positive electrode materials, and in particular relates to a method for preparing a lithium ion battery positive electrode material coated with a solid electrolyte. Background Art

[0002] From the current situation, the application scope of lithium-ion batteries has become more and more extensive. For example, lithium batteries are used in computers, cameras, mobile phones and other devices that can be seen everywhere. At present, the application of lithium-ion batteries in electric vehicles is being developed and utilized. It is expected that lithium-ion battery new energy vehicles may become an indispensable means of transportation in our lives in the future, which can reduce environmental pollution and reduce the loss of fossil energy.

[0003] In lithium-ion batteries, the positive electrode material plays a very important role and has a key influence on the performance of lithium-ion batteries. Layered nickel-cobalt-manganese (aluminum) oxide LiNi x Co y M 1-x-y O2 ternary cathode material combines the advantages of three single metal oxides, Ni, Co and M, and is a promising cathode candidate material. x Co y Mn 1-x-y O2 (x ≥ 0.8) positive electrode materials have the advantages of high capacity and low manufacturing cost. However, due to the characteristics of the material itself, there are also many technical problems, such as surface side reactions and the generation of particle microcracks, which limit the large-scale promotion of its application. Surface coating modification of electrode materials is the most common and effective method to solve the problem of reduced battery cycle life, because the coating layer can effectively protect the active material from external corrosion, thereby increasing the service life of the material. Secondly, the coating layer has a certain influence on the transmission of lithium ions in the electrode material, so it is necessary to find a suitable coating layer.

[0004] Transition metal oxides and phosphides are often used as coating materials because they do not change the structure of the active material, do not participate in the electrochemical reaction, and can protect the active electrode material from the corrosive electrolyte. + Mobility of Li + Conductors have received great attention as stable coatings for cathode materials to overcome the instability of cathode solid electrolyte interface (CEI). LATP is an excellent NASION fast ion conductor with high safety and stability. Therefore, when LATP is coated on the surface of the cathode material, it can not only improve the side reactions between the cathode material and the electrolyte during the cycle and the generation of cracks on the surface of the material by isolating the electrolyte and the cathode material, but also reduce the impedance of lithium ion transfer between the liquid phase and the solid phase, thereby increasing the ion transfer rate.

[0005] CN111755698A discloses a positive electrode material coated with an oxide solid electrolyte and a preparation method thereof, wherein the method first obtains an oxide solid electrolyte precursor solution, then uses the oxide solid electrolyte precursor solution to coat the positive electrode material, and finally sinters the positive electrode material coated with the oxide solid electrolyte precursor solution to obtain the positive electrode material coated with the oxide solid electrolyte. The process is long, and the electrochemical properties of the coated material are not disclosed.

[0006] CN113555544A discloses a high-pressure spinel LiNi co-doped with Al-Ti-Mg elements and coated with LATP. 0.5 Mn 1.5 The preparation method of O4 is to obtain the positive electrode material by wet ball milling the raw materials and then performing secondary sintering; then LATP and the positive electrode material are sintered at high temperature to obtain the positive electrode material.

[0007] The current coating process is complicated, and we need to find a coating process that is simple, easy to operate, has a short cycle, and produces materials with excellent performance that is suitable for industrial-scale production. Summary of the invention

[0008] In view of this, the object of the present invention is to provide a simple and efficient method for preparing a solid electrolyte-coated lithium-ion battery positive electrode material. The solid electrolyte-coated lithium-ion battery positive electrode material provided by the present invention has good rate performance and cycle stability.

[0009] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0010] The present invention provides a method for preparing a lithium-ion battery positive electrode material coated with a solid electrolyte, which specifically comprises the following steps:

[0011] 1) mixing a soluble nickel source, a soluble cobalt source, a soluble manganese (aluminum) source and deionized water to obtain a metal ion solution;

[0012] 2) respectively preparing sodium hydroxide solution and ammonia water, wherein the ammonia water is divided into base ammonia and feed ammonia;

[0013] 3) adding the bottom material ammonia prepared in step 2) into the reactor, and then respectively and simultaneously adding the prepared feed ammonia, sodium hydroxide solution and metal ion solution into the reactor for coprecipitation reaction, and then aging, filtering and drying to obtain the cathode material precursor nickel cobalt manganese (aluminum) hydroxide;

[0014] 4) mixing the solid electrolyte, the cathode material precursor nickel-cobalt-manganese (aluminum) hydroxide and the lithium source by dry grinding to obtain a uniform mixture;

[0015] 5) calcining the mixture in two stages, low temperature and high temperature, to obtain a lithium-ion battery positive electrode material coated with a solid electrolyte.

[0016] The chemical composition of the positive electrode material is LiNi x Co y M 1-x-y O2, where M is Mn or Al, x+y≤1;

[0017] The solid electrolyte is lithium aluminum titanium phosphate (LATP).

[0018] Preferably, the mass ratio of the solid electrolyte LATP to the positive electrode material is 0.005-0.05:1.

[0019] Preferably, the thickness of the solid electrolyte LATP is 1 to 10 nm;

[0020] The particle size of the lithium-ion battery positive electrode material coated with the solid electrolyte LATP is 1 to 8 μm.

[0021] Preferably, the manganese (aluminum) source, cobalt source and nickel source are soluble metal salts (such as sulfate, acetate, etc.).

[0022] Preferably, the concentration of the metal ion solution is 1-3 mol / L, the concentration of the sodium hydroxide solution is 2-6 mol / L, the concentration of the bottom liquid ammonia solution is 0.4-0.6 mol / L, the concentration of the feed ammonia solution is 2-3.5 mol / L, and nitrogen is introduced into the reactor.

[0023] Preferably, the pH value of the coprecipitation reaction is 9-11; the temperature of the coprecipitation reaction is 45-65°C; the coprecipitation reaction is carried out under stirring, and the stirring speed is 400-1000rpm; the aging time of the coprecipitation reaction is 1-5h, and the stirring speed during aging is 200-400rpm; the drying temperature is 80°C-120°C, and the drying time is 12-24h.

[0024] Preferably, the lithium source is lithium hydroxide monohydrate, lithium carbonate, lithium nitrate or lithium acetate.

[0025] Preferably, the molar ratio of the lithium element in the lithium source to the nickel, cobalt, and manganese (aluminum) elements in the nickel-cobalt-manganese (aluminum) hydroxide precursor satisfies n(Li):n(Ni+Co+M)=1.01-1.1:1.

[0026] Preferably, the grinding is carried out by dry or wet grinding mixing, and the mixing time is 20 to 30 minutes.

[0027] Preferably, the temperature of the low-temperature calcination is 400-700°C, and the holding time is 4-7h; the temperature of the high-temperature calcination is 700-900°C, and the holding time is 10-15h; the heating rate to the calcination temperature is preferably 4-10°C / min; the two-stage calcination is preferably carried out under an oxygen atmosphere.

[0028] Furthermore, the present invention also seeks to protect the use of the high-nickel material coated with the solid electrolyte LATP prepared by the above method in lithium-ion batteries.

[0029] Specifically, the modified high-nickel material is used as a positive electrode material for a lithium-ion battery.

[0030] It can be seen from the above technical solution that, compared with the prior art, the method for preparing a solid electrolyte-coated lithium-ion battery positive electrode material provided by the present invention has the following excellent effects:

[0031] 1. The present invention provides a method for preparing the above-mentioned solid electrolyte coated lithium ion battery positive electrode material. The present invention adopts a solid phase method to prepare the solid electrolyte coated lithium ion battery positive electrode material. The precursor, LATP and lithium source are directly mixed and calcined in one step to obtain the positive electrode material coated on the surface of the solid electrolyte by the solid phase method. The method is simple, short cycle, low cost, uniform coating, and easy to achieve mass production.

[0032] 2. The present invention provides a lithium-ion battery positive electrode material coated with a solid electrolyte prepared by the above method, comprising a positive electrode material and a solid electrolyte coated on the surface of the positive electrode material; the chemical composition of the positive electrode material is LiNi x Co y M 1-x-y O2, wherein M is Mn or Al, x+y≤1; the solid electrolyte is lithium titanium aluminum phosphate. The present invention coats a layer of lithium titanium aluminum phosphate on the surface of the positive electrode material of the lithium ion battery, which can not only prevent the direct contact between the active electrode material and the electrolyte, but also prevent the side reaction between the electrode material and the electrolyte and the corrosion of the electrode material by the decomposition products of the electrolyte, and significantly improve the stability of the material during the cycle; and, because lithium titanium aluminum phosphate has strong ionic conductivity, it improves the lithium ion transmission rate, thereby improving the discharge specific capacity and rate performance of the positive electrode material of the lithium ion battery. After 100 cycles at a rate of 1C, the NCM811@1%LATP material shows 174.16mAh·g -1 The discharge specific capacity and capacity retention rate of 95.19% are achieved.

[0033] Combining the above advantages, solid electrolyte-coated lithium-ion battery positive electrode materials have broad application prospects in fields such as portable electronic devices and electric vehicles, and are expected to further promote the development of lithium-ion battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0035] Figure 1 LiNi is a positive electrode material of a lithium ion battery coated with different contents of LATP obtained in Example 1, Example 2, Example 3, Example 4 and Comparative Example 1. 0.8 Co 0.1 Mn 0.1 SEM image of O2.

[0036] Figure 2 The positive electrode material LiNi coated with LATP obtained in Example 2 and Comparative Example 1 is 0.8 Co 0.1 Mn 0.1 TEM image of O2.

[0037] Figure 3 The positive electrode material LiNi coated with LATP obtained in Example 1, Example 2, Example 3, Example 4 and Comparative Example 1 is 0.8 Co 0.1 Mn 0.1 XRD pattern of O2.

[0038] Figure 4 The positive electrode material LiNi coated with LATP obtained in Example 1, Example 2, Example 3, Example 4 and Comparative Example 1 is 0.8 Co 0.1 Mn 0.1 Cycle curve and rate performance diagram of O2.

[0039] Figure 5 The lithium-ion battery positive electrode material LiNi coated with LATP obtained in Example 1, Example 2, Example 3 and Comparative Example 1 0.8 Co 0.1 Mn 0.1 AC impedance diagram of O2. DETAILED DESCRIPTION

[0040] The following will be combined with the embodiments of the present invention and the drawings of the specification to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The embodiment of the invention discloses a method for preparing a lithium-ion battery positive electrode material coated with a solid electrolyte.

[0042] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.

[0043] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0044] Example 1

[0045] (1) Preparation of precursors: Prepare nickel sulfate, cobalt sulfate, and manganese sulfate raw materials, and prepare 750 mL of solution A with a metal ion concentration of 2 mol / L according to the molar ratio of Ni, Co, and Mn of 0.8:0.1:0.1; - Weigh NaOH in a molar ratio of 1:2 and prepare 250 ml of 4 mol / L NaOH solution; prepare 250 ml of 3.5 mol / L ammonia solution B.

[0046] Solution A and solution B were slowly added to the reactor at a feed rate of 3:1, and the pH value of the reaction process was controlled to be 11.4-11.6, the temperature was 55°C, and the stirring speed was 600 rpm. After the reaction, the mixture was aged for 3 hours, filtered, and dried to obtain a LiNi 0.8 Co 0.1 Mn 0.1 Nickel cobalt manganese hydroxide precursor powder for lithium-ion battery cathode material of O2.

[0047] (2) Using LATP (Li 1.3 Al 0.3 Ti 1.7 (PO4)3) (Chinese medicine, 99.99%), the nickel cobalt manganese hydroxide precursor prepared above (Ni 0.8 Co 0.1 Mn 0.1(OH)2) and lithium source LiOH.H2O (Aladdin, 98%) are used as raw materials, a lithium source and a nickel cobalt manganese hydroxide precursor with a molar ratio of 1.05:1 are added to a mortar, and then LATP with a mass ratio of 0.005 to the nickel cobalt manganese hydroxide precursor is added to prepare LATP-modified lithium-ion battery positive electrode materials with different coating contents. After grinding in a mortar for 30 minutes, it is placed in an oxygen-permeable tubular furnace for pre-sintering at 480°C for 5 hours, and then calcined at 750°C for 12 hours to prepare a LATP-coated modified NCM811 positive electrode material (marked as: NCM811@0.5%LATP).

[0048] Example 2

[0049] In Example 1, Ni 0.8 Co 0.1 Mn 0.1 (OH)2 positive electrode material precursor and lithium source LiOH.H2O (Aladdin, 98%) are used as raw materials, and the lithium source and nickel cobalt manganese hydroxide precursor with a molar ratio of 1.05:1 are added to a mortar, and then LATP with a mass ratio of 0.01:1 to the nickel cobalt manganese hydroxide precursor is added to prepare LATP-modified lithium-ion battery positive electrode materials with different coating contents. After grinding in a mortar for 30 minutes, it is placed in an oxygen-permeable tubular furnace and pre-sintered at 480°C for 5 hours, and then calcined at 750°C for 12 hours to prepare LATP-coated modified NCM811 positive electrode material (marked as: NCM811@1%LATP).

[0050] Example 3

[0051] In Example 1, Ni 0.8 Co 0.1 Mn 0.1 (OH)2 positive electrode material precursor and lithium source LiOH.H2O (Aladdin, 98%) are used as raw materials, and the lithium source and nickel cobalt manganese hydroxide precursor with a molar ratio of 1.05:1 are added to a mortar, and then LATP with a mass ratio of 0.02:1 to the nickel cobalt manganese hydroxide precursor is added to prepare LATP-modified lithium-ion battery positive electrode materials with different coating contents. After grinding in a mortar for 30 minutes, it is placed in an oxygen-permeable tubular furnace and pre-sintered at 480°C for 5 hours, and then calcined at 750°C for 12 hours to prepare LATP-coated modified NCM811 positive electrode material (marked as: NCM811@2%LATP).

[0052] Example 4

[0053] In Example 1, Ni 0.8 Co 0.1 Mn 0.1(OH)2 positive electrode material precursor and lithium source LiOH.H2O (Aladdin, 98%) are used as raw materials, and the lithium source and nickel cobalt manganese hydroxide precursor with a molar ratio of 1.05:1 are added to a mortar, and then LATP with a mass ratio of 0.03:1 to the nickel cobalt manganese hydroxide precursor is added to prepare LATP-modified lithium-ion battery positive electrode materials with different coating contents. After grinding in a mortar for 30 minutes, it is placed in an oxygen-permeable tubular furnace and pre-sintered at 480°C for 5 hours, and then calcined at 750°C for 12 hours to prepare LATP-coated modified NCM811 positive electrode material (marked as: NCM811@3%LATP).

[0054] Comparative Example 1

[0055] (1) According to the method of step (1) of Example 1, a LiNi 0.8 Co 0.1 Mn 0.1 O2 nickel cobalt manganese hydroxide precursor powder, the obtained precursor powder and lithium source LiOH.H2O grinding and mixing, the amount ratio of LiOH.H2O to the ternary precursor material is n(Li):n(Ni+Co+Mn)=1.05:1; the obtained mixture is pre-sintered at 480°C for 5h in an oxygen atmosphere, and then sintered at 750°C for 12h to obtain a LiNi 0.8 Co 0.1 Mn 0.1 High nickel lithium ion positive electrode material for O2 (labeled as: p-NCM811).

[0056] The following is a structural characterization and performance measurement of the materials prepared in the above examples and comparative examples. The specific experimental contents are as follows:

[0057] (I) SEM image analysis

[0058] LATP solid phase coating modified high nickel lithium ion cathode material LiNi 0.8 Co 0.1 Mn 0.1 The SEM image of O2 is as follows Figure 1 shown. Figure 1 (a1, a2) p-NCM811, (b1, b2) NCM811@0.5% LATP, (c1, c2) NCM811@1% LATP, (d1, d2) NCM811@2% LATP, (e1, e2) NCM811@3% LATP. It can be seen from the figure that with the increase of coating content, when the coating content increases from 0.5% to 3%, the particle surface of the sample gradually becomes blurred, the gaps between the primary particles become gradually blurred, and flocculent substances exist on the particle surface, indicating that LATP is successfully coated on the surface of NCM811.

[0059] (II) TEM image analysis

[0060] LATP solid phase coating modified high nickel lithium ion cathode material LiNi 0.8 Co 0.1 Mn 0.1 The TEM image of O2 is as follows Figure 2 As shown. In Figure (a), the surface of the p-NCM811 particles is smooth, and there is no other material on the edge of the particles. After performing FFT on the local area A, the parallel lattice fringes of the material can be clearly obtained. The measured lattice spacing is 0.47nm, corresponding to the (003) characteristic lattice plane in the p-NCM811 layered structure. Figure (b) is a TEM image of NCM811@1%LATP. It can be seen that there is a coating with a thickness of 5-8nm on the surface. FFT was performed on local areas B and C, and it can be obtained that the lattice fringes spacing of the internal matrix material p-NCM811 remains unchanged, indicating that the LATP coating modification does not affect the crystal structure of the matrix material. At the same time, the stripes in the edge area C are measured to have a spacing of 0.27nm, corresponding to the (211) crystal plane of LATP, indicating the existence of the LATP coating layer and confirming that LATP is successfully coated on the surface of NCM811.

[0061] (III) XRD spectrum analysis

[0062] LATP solid phase coating modified high nickel lithium ion cathode material LiNi 0.8 Co 0.1 Mn 0.1 The XRD pattern of O2 is as follows Figure 3 As shown. Figure (a) shows that no impurity peaks were detected in all samples, and no LATP peaks were observed due to the low content. Figure (b) shows the enlarged spectrum of some characteristic peaks of the samples. It can be seen from the figure that with the gradual increase of the LATP coating amount, the (003) peak and the (104) peak shift to the low-angle side. This is due to the trace diffusion of the solid electrolyte LATP component to the material surface during the sintering process.

[0063] (IV) Electrochemical performance test

[0064] Figure 4 LiNi is a high nickel lithium ion cathode material coated and modified by LATP solid phase method 0.8 Co 0.1 Mn 0.1 The cycling curve and rate performance diagram of O2. The electrochemical test results show that the LATP coating with a mass fraction of 1% has the best electrochemical performance. At 2.7-4.3V, after 100 cycles, the discharge capacity of NCM811@1%LATP is 174.16mAh·g -1 Compared with the 114.1 mAh g of unmodified p-NCM811-1 60.06 mAh g higher -1 , NCM811@1%LATP exhibited the highest capacity retention of 95.19% after 100 cycles, while the unmodified p-NCM811 exhibited a retention of 66.6% after 100 cycles, thus proving that 1wt% is the optimal coating amount for LATP-coated modified NCM811.

[0065] Figure 5 LiNi is a high nickel lithium ion cathode material coated and modified by LATP solid phase method 0.8 Co 0.1 Mn 0.1 AC impedance diagram of O2. The NCM811@1%LATP sample has low impedance and high lithium ion transfer coefficient, thus showing excellent cycle stability and rate performance.

[0066] The present invention includes but is not limited to the above embodiments. Any equivalent replacement or partial improvement made under the principle of the spirit of the present invention shall be deemed to be within the protection scope of the present invention.

[0067] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a lithium-ion battery positive electrode material coated with a solid electrolyte, characterized in that: The specific steps include: 1) mixing a soluble nickel source, a soluble cobalt source, a soluble manganese source or an aluminum source with deionized water to obtain a metal ion solution; 2) respectively preparing sodium hydroxide solution and ammonia water, wherein the ammonia water is divided into base ammonia and feed ammonia; 3) adding the bottom material ammonia prepared in step 2) into the reactor, and then respectively adding the prepared feed ammonia, sodium hydroxide solution and metal ion solution into the reactor at the same time for coprecipitation reaction, and then aging, filtering and drying to obtain the positive electrode material precursor nickel cobalt manganese hydroxide or nickel cobalt aluminum hydroxide; The pH value of the coprecipitation reaction is 9-11; the temperature of the coprecipitation reaction is 45-65°C; the coprecipitation reaction is carried out under stirring, and the stirring speed is 400-1000rpm; the aging time of the coprecipitation reaction is 1-5h, and the stirring speed during aging is 200-400rpm; the drying temperature is 80°C-120°C, and the drying time is 12-24h; The concentration of the metal ion solution is 1-3 mol / L, the concentration of the sodium hydroxide solution is 2-6 mol / L, the concentration of the bottom liquid ammonia solution is 0.4-0.6 mol / L, the concentration of the feed ammonia solution is 2-3.5 mol / L, and nitrogen is introduced into the reactor; 4) grinding and mixing the solid electrolyte, the cathode material precursor nickel cobalt manganese hydroxide or nickel cobalt aluminum hydroxide and the lithium source to obtain a uniform mixture; The grinding and mixing time is 20 to 30 minutes; 5) calcining the mixture in two stages, at low temperature and high temperature, to obtain a lithium-ion battery positive electrode material coated with a solid electrolyte; The solid electrolyte coated lithium ion battery positive electrode material comprises a positive electrode material and a solid electrolyte coated on the surface of the positive electrode material; The chemical composition of the positive electrode material is LiNi x Co y M 1-x-y O2, where M is Mn or Al, x+y≤1; The solid electrolyte is lithium aluminum titanium phosphate (LATP); The mass ratio of the solid electrolyte LATP to the positive electrode material is 0.005-0.01:

1.

2. The solid electrolyte coated lithium ion battery positive electrode material according to claim 1, characterized in that: The thickness of the solid electrolyte LATP is 1 to 10 nm; The particle size of the lithium-ion battery positive electrode material coated with the solid electrolyte LATP is 1 to 8 μm.

3. The method for preparing a lithium-ion battery positive electrode material coated with a solid electrolyte according to claim 1, characterized in that: The lithium source is lithium hydroxide monohydrate, lithium carbonate, lithium nitrate or lithium acetate.

4. The method for preparing a lithium-ion battery positive electrode material coated with a solid electrolyte according to claim 1, characterized in that: The temperature of the low-temperature calcination is 400-700°C, and the holding time is 4-7h; The high temperature calcination temperature is 700-900° C., and the heat preservation time is 10-15 hours.

Citation Information

Patent Citations

  • Oxide solid electrolyte coated positive electrode material and preparation method thereof

    CN111755698A

  • Al-Ti-Mg element co-doped and LATP-coated high-voltage spinel LNMO positive electrode material and preparation method thereof

    CN113555544A

  • Flexible interface coated positive electrode material and solid-state battery

    CN114899372A